The intersection of disability status and rurality in American Indian/Alaskan Native communities - Mashinchi, Genna M.; Hicks, Emily C.; Leopold, Arin J.; Greiman, Lillie; Ipsen, Catherine (Frontiers in Rehabilitation Sciences, 2022)
There is a noteworthy gap in the literature regarding disability in rural American Indian/Alaskan Native (AI/AN) communities. This is significant, as many tribal lands are in rural area and AI/AN individuals report some of the highest rates of disability. To fill the existing gap in the literature, we used descriptive statistics and a linear regression analysis to examine disability and rurality in AI/AN communities and to better understand the intersection of these disparities. Results indicate that rural counties have the highest rates of disability for both Whites and AI/AN. AI/AN communities have higher rates than Whites. However, further analysis indicates that county makeup (counties with high rates of AI/AN in the general population) interacted with the relationship between rural and disability for AI/AN populations. Rural counties with higher rates of AI/AN report lower rates of disability relative to Whites. Further analysis is needed to unpack this relationship, but results suggest that AI/AN communities play a protective role, moderating the amount of disability experienced in rural AIAN communities.